Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Sma Swasta St. Antonius Bangun Mulia - Frans Joko Gultom; Israil Sitepu; Frida Marta Simorangkir (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to find out whether the application of the Student Teams Achievement Division (STAD) type cooperative learning model can improve the mathematical problem solving abilities of students at St. Private High School. Antonius Bangun Mulia. This research method uses Classroom Action Research (PTK). The research procedure is cyclical. Each cycle consists of 4 stages, namely: planning, implementing actions, observing and reflecting. Data collection techniques through observation and tests. This data collection uses several instruments in the form of teacher observation sheets and student observation sheets. Meanwhile, to determine students' mathematical problem solving abilities, tests are used. The results of the research show that the use of the Student Teams Achievement Division (STAD) type cooperative learning model can improve students' mathematical problem solving abilities in mathematics lessons on Systems of Three Variable Linear Equations (STVLE). From the average value of prerequisite abilities, namely 42, the average value of students' mathematical problem solving abilities in cycle I is 67 and the average value of students' mathematical problem solving abilities in cycle II is 76 and the value of teacher and student activities in cycle I is 63% and 58%, and cycle II, namely 80% and 82%.